1979
DOI: 10.1128/aem.37.3.438-442.1979
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Vibrio parahaemolyticus in Dutch mussels

Abstract: A study was carried out on the occurrence of Vibrio parahaemolyticus in Dutch mussels originating from the East Schelde Estuary. In a total of 79 10-g tissue samples, 3 (3.8%) were found to contain V. parahaemolyticus. In a second survey, 6 out of 23 bags of mussels (26%) contained one or more strains of V. parahaemolyticus in 5-g tissue samples. The many limitations of current methodology used in such surveys are stressed. Positive samples can be missed because viable cells may die during refrigerated transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Both characteristics were only observed when strains were grown at their optimal temperature and, for H2S production, in a medium containing 3% NaCl. This is in agreement with other authors, who concluded that NaCI tolerance and H,S production depend on various parameters such as temperature, duration of incubation, and nutrient composition of the medium (14,15). Thus, ability to grow in a 10% NaClcontaining broth is not specific enough to reject an identification as V. pairahaernolytisus.…”
supporting
confidence: 91%
“…Both characteristics were only observed when strains were grown at their optimal temperature and, for H2S production, in a medium containing 3% NaCl. This is in agreement with other authors, who concluded that NaCI tolerance and H,S production depend on various parameters such as temperature, duration of incubation, and nutrient composition of the medium (14,15). Thus, ability to grow in a 10% NaClcontaining broth is not specific enough to reject an identification as V. pairahaernolytisus.…”
supporting
confidence: 91%